A polypeptide drug carrier for maternal delivery and prevention of fetal exposure. (December 2014) - George, Eric M.; Liu, Huiling; Robinson, Grant G.; Bidwell, Gene L.
Abstract Background: Pregnant females are largely overlooked in drug development due to concerns for fetal health. Additionally, pregnancy is often an exclusion criterion in clinical trials, so the safety of many drugs during pregnancy is unknown. Purpose: The goal of this study was to evaluate Elastin-like Polypeptide (ELP), a synthetic protein derived from human elastin, for maternally sequestered drug delivery. ELP is a versatile drug carrier with a long plasma half-life, low immunogenicity, and the ability to be fused to nearly any small molecule or protein-based therapeutic. Methods: We determined the pharmacokinetics, biodistribution, and fetal exposure to the ELP drug carrier using quantitative fluorescence techniques in a rat pregnancy model. Results: After either bolus IV administration or continuous infusion over five days, ELPs accumulated strongly in the kidneys, liver, and placenta, but importantly, little to no ELPs were detectable in the fetus. Within the placenta, ELPs were localized to the chorionic plate and broadly distributed within the labyrinth, but were excluded from the fetal portion of the chorionic villi. Conclusion: These data indicate that ELP does not cross the placenta, and they suggest that this adaptable drug delivery system is a promising platform for prevention of fetal drug exposure.